2017
DOI: 10.1371/journal.pone.0176496
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-modifying agents convert fibroblasts to OCT4+ and VEGFR-2+ capillary tube-forming cells

Abstract: RationaleThe human epigenome is plastic. The goal of this study was to address if fibroblast cells can be epigenetically modified to promote neovessel formation.Methods and resultsHere, we used highly abundant human adult dermal fibroblast cells (hADFCs) that were treated with the chromatin-modifying agents 5-aza-2'-deoxycytidine and trichostatin A, and subsequently subjected to differentiation by activating Wnt signaling. Our results show that these epigenetically modified hADFCs increasingly expressed β-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Cardiac fibroblasts were once thought to be terminally differentiated cells. However, recent studies have shown that chromatin-modifying agents could activate Wnt signaling to transform human adult dermal fibroblast cells to OCT4+ and VEGFR-2+ capillary tube-forming cells [3]. When pathological damage occurs in the heart, fibroblasts undergo a mesenchymal-endothelial transition (MEndoT) to obtain endothelial cell-like functions and participate in angiogenesis in the cardiac injury area, which is a novel antifibrotic strategy to alleviate myocardial fibrosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac fibroblasts were once thought to be terminally differentiated cells. However, recent studies have shown that chromatin-modifying agents could activate Wnt signaling to transform human adult dermal fibroblast cells to OCT4+ and VEGFR-2+ capillary tube-forming cells [3]. When pathological damage occurs in the heart, fibroblasts undergo a mesenchymal-endothelial transition (MEndoT) to obtain endothelial cell-like functions and participate in angiogenesis in the cardiac injury area, which is a novel antifibrotic strategy to alleviate myocardial fibrosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…5-Aza-2 ′ -deoxycytidine, a DNA methyltransferase inhibitor, and trichostatin A, a histone deacetylase inhibitor, may cause chromatin decondensation and induce a short "dedifferentiation" state. Tideglusib inhibited β-catenin phosphorylation, which resulted in its translocation to the nucleus activation of Wnt signaling, thus causing the differentiation [73]. These results illustrate the feasibility of direct reprogramming for obtaining endothelial cells by bioactive molecule induction, but more achievable paths and the critical signaling pathways for reprogramming need to be further explored.…”
Section: Endothelial Cells Derived By Bioactive Moleculementioning
confidence: 78%